Pengaruh Gaya Kepemimpinan terhadap Kinerja Pegawai Dinas Penyelamatan Pemadam Kebakaran (PPK) di Kota Palembang - Suryadi Suryadi (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2017)
The influence of leadership style to work performance of project workers at Dinas Penyelamatan Pemadam Kebakaran (PPK) at Palembang City. This reseach is made for knowing the influence of leadership style to work performance simultaneously. This reseach Usesndesign survey by collecting information from respondents using list of questionnaire structurally that depends on the needs and related with the tittle of this reseeach. The variable of this reseach are leadership style varisble (X1), and work performance variable (Y). This reseach in volves 50 respondents. The instruments for leadersip style, work performance of project worker are validatet by formula of product moment correlation. The reability instrument is using alpha cronbach and for the analize, it,s using regression. The research results showed that leadership style variable les have positive influences for work performance of project staff at Dinas Penyelamatan Pemadam Kebakaran (PPK) at Palembang City even partially.